The Applications of Traditional Javanese Architecture with Javanese Philosophy for East Java Cultural Attractions Complex in Surabaya - A W Ekaraga; W W Widjajanti; B W Sulistyo (IPTEK Journal of Proceedings Series, 2018)
"Wong Jawa Ilang Jawane” (“Javanese people were losing their Javaneseness”) is an expression which refers to Javanese youngsters that adapting western culture. Therefore, this study an attempts to offer “Javaneseness” concept for Javanese tribe to reflect. The researchers are using descriptive method. The researchers are using tourist attractions standards and the cultural attractions. The applications of “Traditional javanese Architecture” theme will be the vessel of four cultural tlatah (areas) from East Java, and referring to “Manunggaling Kawula Gusti” as the theoretical framework from Javanese philosophy for cultural attractions complex in Surabaya.